Association of radiographic osteoarthritis, pain on passive movement and knee range of motion: A cross-sectional study. Issue 2 (April 2015) - Hilfiker, Roger; Jüni, Peter; Nüesch, Eveline; Dieppe, Paul A.; Reichenbach, Stephan
Abstract: Background: Knee pain is associated with radiographic knee osteoarthritis, but the relationships between physical examination, pain and radiographic features are unclear. Objective: To examine whether deficits in knee extension or flexion were associated with radiographic severity and pain during clinical examination in persons with knee pain or radiographic features of osteoarthritis. Design: Cross-sectional data of the Somerset and Avon Survey of Health (SASH) cohort study. Methods: Participants with knee pain or radiographic features of osteoarthritis were included. We assessed the range of passive knee flexion and extension, pain on movement and Kellgren and Lawrence (K/L) grades. Odds ratios were calculated for the association between range of motion and pain as well as radiographic severity. Results/findings: Of 1117 participants with a clinical assessment, 805 participants and 1530 knees had complete data and were used for this analysis. Pain and radiographic changes were associated with limited range of motion. In knees with pain on passive movement, extension and flexion were reduced per one grade of K/L by −1.4° (95% CI −2.2 to −0.5) and −1.6° (95% CI −2.8 to −0.4), while in knees without pain the reduction was −0.3° (95% CI -0.6 to −0.1) (extension) and −1.1° (−1.8 to −0.3) (flexion). The interaction of pain with K/L was significant ( p = 0.021) for extension but not for flexion ( p = 0.333). Conclusions: Pain during passive movement, which may be an indicator of reversible soft-tissue changes, e.g., reversible through physical therapy, is independently associated with reduced flexion and extension of the knee.